STATE AND DYNAMICS OF THE STRENGTH ABILITIES OF PRESCHOOL CHILDREN - Ts. Traykova (Trakia Journal of Sciences)
The period of pre-school age is characterized by an intensive growth and development of the human organism. In that connection, we set the aim of our study: to investigate the development of the strength abilities of children from a preparatory group for school (5-7 years old) as a result of the application of physical culture enriched educational program (for the period of one school year). The investigated subjects were 208 children from two kindergartens and one school in the city of Sofia. The following methods were used: Theoretical analysis, pedagogical experiment, pedagogical testing, and statistical methods. The following motor fitness tests were used: hand grip (left and right hand), standing broad jump, throwing 1 kg medicine ball with two hands above head, throwing 1 kg medicine ball with two hands underneath, throwing a small dense ball as far as possible, and maximum number of squats for 20 sec. From the results obtained, it was found that the greatest increase in strength abilities was found in the children of the experimental test groups as follows: ‘Throwing a small dense ball’, ‘left hand grip’, ‘throwing 1 kg medicine ball with two hands above head’. Results: As a result of the training methodology applied, an increase in the strength abilities of the children of both sexes was established.